Conjugative Selectivity of Plasmids Is Affected by Coexisting Recipient Candidates - Sakuda, Ayako (mSphere, 2018)
Understanding the mechanisms underlying plasmid behavior under conditions of various environments is important to predict the fate of plasmids in nature. Most previous studies on plasmid transfer employed two strains: one as a donor and the other as a recipient. However, in natural environments, there are usually different recipient cells available to which plasmid can be transferred. In this study, to reveal the underlying mechanisms, we assessed the transferability of plasmids from one donor strain to either of two recipient candidates as the most simplified model. We used Pseudomonas putida KT2440 and Pseudomonas resinovorans CA10dm4 as model hosts and pCAR1 (IncP-7), NAH7 (IncP-9), pB10 (IncP-1β), and R388 (IncW) as model plasmids. As expected, in most cases these plasmids were generally transferred more frequently to a recipient of the same species than to a recipient of a different one under conditions of liquid and filter mating, although NAH7 was transferred from P. resinovorans more frequently to P. putida than to P. resinovorans during filter mating. With the exception of pCAR1, which was less affected, the coexistence of other recipients enhanced the preferences of conjugative transfer to the same species. In particular, preferences corresponding to transfer from P. putida to a different recipient (P. resinovorans) were reduced by the presence of a coexisting same recipient (P. putida) during transfer of NAH7 in liquid and transfer of R388 in filter mating. We determined that large cell aggregates and substances secreted into culture supernatant were not responsible for this phenomenon. Overall, the results of this study suggest the existence of unknown factors determining optimal plasmid transfer to native recipients. IMPORTANCE Most previous studies on plasmid conjugal transfer employed experimental setups with two strains: one as a donor and the other as a recipient. However, the results obtained sometimes failed to agree with observations obtained under natural environmental conditions or in a model microcosm using natural soil and water samples. Therefore, we consider that there is a “gap” in our understanding of plasmid behavior in the context of bacterial consortia that exist under the actual environmental conditions. In this study, we clearly showed that the conjugation selectivity of a plasmid can be affected by the recipient candidates existing around the donor strain by the use of a simplified experimental setup with one strain as the donor and two strains as recipients. These phenomena could not be explained by factors known to affect plasmid transfer as suggested by previous studies. Therefore, we suggest the presence of novel elements regulating plasmid transfer within consortia.